PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM BELAJAR TERHADAP DAYA SAING SATUAN PENDIDIKAN NON FORMAL PENYELENGGARA PROGRAM KESETARAAN DI KOTA MATARAM - Rosi Jayadi; Sudirman Sudirman; Abdul Kadir Jaelani; Muhammad Makki; Dadi Setiadi (STKIP Pesisir Selatan, 2026)
This experimental study aims to analyze the influence of school principal leadership and learning climate on the competitiveness of non-formal education (NFE) institutions offering equivalency programs in Mataram City. The study employs a quantitative approach with an experimental design. Data were collected through a questionnaire that had been tested for validity and reliability, with respondents consisting of 56 teachers and educational staff as well as 56 students from 8 NFE units (1 SKB and 7 PKBM) in Mataram City. Data analysis used multiple linear regression. The results showed that, simultaneously, school principal leadership and learning climate significantly influenced the competitiveness of NFE institutions with a calculated F-value of 20.744 and a significance level of 0.000 (p < 0.01), contributing 43.9%. Partially, school principal leadership has a positive and significant effect on competitiveness (β = 0.668; p = 0.000), while the learning climate does not have a significant effect (β = -0.028; p = 0.793). The findings of this study reveal that in the context of non-formal education units in Mataram City, school principal leadership is the primary driver of competitiveness, while a learning climate that is already good and relatively homogeneous does not directly serve as a significant differentiator.